Spatiotemporal nexus between vegetation change and extreme climatic indices and their possible causes of change. (1st July 2021) - Islam, Abu Reza Md Towfiqul; Islam, H.M.Touhidul; Shahid, Shamsuddin; Khatun, Mst Khadiza; Ali, Mir Mohammad; Rahman, M.Safiur; Ibrahim, Sobhy M.; Almoajel, Alia M.
Abstract: Climate extremes have a significant impact on vegetation. However, little is known about vegetation response to climatic extremes in Bangladesh. The association of Normalized Difference Vegetation Index (NDVI) with nine extreme precipitation and temperature indices was evaluated to identify the nexus between vegetation and climatic extremes and their associations in Bangladesh for the period 1986–2017. Moreover, detrended fluctuation analysis (DFA) and Morlet wavelet analysis (MWA) were employed to evaluate the possible future trends and decipher the existing periodic cycles, respectively in the time series of NDVI and climate extremes. Besides, atmospheric variables of ECMWF ERA5 were used to examine the casual circulation mechanism responsible for climatic extremes of Bangladesh. The results revealed that the monthly NDVI is positively associated with extreme rainfall with spatiotemporal heterogeneity. Warm temperature indices showed a significant negative association with NDVI on the seasonal scale, while precipitation and cold temperature extremes showed a positive association with yearly NDVI. The DEA revealed a continuous increase in temperature extreme in the future, while no change in precipitation extremes. NDVI also revealed a significant association with extreme temperature indices with a time lag of one month and with precipitation extreme without time lag. Spatial analysis indicated insensitivity of marshy vegetation type to climate extremes in winter. The study revealed that elevated summer geopotential height, no visible anticyclonic center, reduced high cloud cover, and low solar radiation with higher humidity contributed to climatic extremes in Bangladesh. The nexus between NDVI and climatic extremes established in this study indicated that increasing warm temperature extremes due to global warming might have severe implications on Bangladesh's ecology and the environment in the future. Graphical abstract: Image 1 Highlights: Nexus between vegetation and climate extremes has explored in Bangladesh. The response lag between NDVI and temperature extreme was higher than precipitation extreme. Marshy vegetation type was insensitive to climate extremes in winter. Extreme temperature limits vegetation growth in the northwest but the impact varied with vegetation types.